2024
DOI: 10.3390/antibiotics13030287
|View full text |Cite
|
Sign up to set email alerts
|

High-Loading-Dose Colistin with Nebulized Administration for Carbapenem-Resistant Acinetobacter baumannii Pneumonia in Critically Ill Patients: A Retrospective Cohort Study

Wasan Katip,
Ajaree Rayanakorn,
Chuleegone Sornsuvit
et al.

Abstract: Carbapenem-resistant Acinetobacter baumannii (CRAB) infections pose a serious threat, with high morbidity and mortality rates. This retrospective cohort study, conducted at Nakornping Hospital between January 2015 and October 2022, aimed to evaluate the efficacy and safety of a high loading dose (LD) of colistin combined with nebulized colistin in critically ill patients with CRAB pneumonia. Of the 261 patients included, 95 received LD colistin, and 166 received LD colistin with nebulized colistin. Multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These factors, as well as age group and employment as nosocomial infection control personnel, regular supervision, and the number of training sessions per year, were also associated with self-reported practice. [44][45][46] Additionally, there was a study conducted by Ogoina et al 43 in Africa in Nigeria that found that overall, there was a strong relationship between age, years of experience, and antibiotic resistance knowledge. Also, a study found that there were factors influencing practice including consistent medical staff turnover, an absence of "pediatric competent" nurses and doctors, lower senior healthcare coverage after hours, and time constraints in emergency departments.…”
Section: Discussionmentioning
confidence: 99%
“…These factors, as well as age group and employment as nosocomial infection control personnel, regular supervision, and the number of training sessions per year, were also associated with self-reported practice. [44][45][46] Additionally, there was a study conducted by Ogoina et al 43 in Africa in Nigeria that found that overall, there was a strong relationship between age, years of experience, and antibiotic resistance knowledge. Also, a study found that there were factors influencing practice including consistent medical staff turnover, an absence of "pediatric competent" nurses and doctors, lower senior healthcare coverage after hours, and time constraints in emergency departments.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Carbapenem-resistant Enterobacteriaceae infections pose a major threat to human health due to limited treatment options. Colistin-based regimens have become a major treatment option, 32 , 33 and long courses of colistin therapy have reduced 30-day mortality in critically ill patients. 34 However, Huang et al showed that patients who received nebulized colistin had a relatively high proportion of Elizabethkingia spp.…”
Section: Discussionmentioning
confidence: 99%